Line profile-based fingerprint matching - Ali, Hafsa Moontari; Corraya, Sonia (© 2017 Institute of Electrical and Electronics Engineers Inc., 2018)
This conference paper was published in the IWCI 2016 - 2016 International Workshop on Computational Intelligence [© 2016 IEEE.] and the definitive version is available at: http://doi.org/10.1109/IWCI.2016.7860350 The Journal's website is at: http://ieeexplore.ieee.org/document/7860350/?reload=true